Negotiating Religious Authority in a Masculine Space: Gender Regime and Female Leadership in an NU Pesantren - Isma Malicha; Erna Dwi Nugraini; Muhammad Yusuf Fadhil; Azis Azis (Universitas Islam Negeri Madura, 2026)
This article examines the leadership of Nyai Hj. Masriyah Amva at Pesantren Kebon Jambu Al-Islamy as a negotiated reconstruction of religious authority within the patriarchal structure of traditional Nahdlatul Ulama pesantren. Drawing on Raewyn Connell’s gender regime theory, the study conceptualizes pesantren not as rigid institutions but as social spaces in which gendered authority is continuously produced and contested. Based on a qualitative case study involving in-depth interviews, participant observation, and document analysis, this article shows that sufi spirituality, religious poetry, and symbolic practices function as key sources of legitimacy that enable Nyai Masriyah to exercise leadership without directly confronting established institutional norms. Her spiritual experience and ethical authority gradually reconfigure male-dominated leadership arrange-ments by opening space for women’s participation within accepted religious frameworks. This study contributes to gender and Islamic studies by demonstrating how spiritual authority operates as a context-specific resource for institutional transformation, positioning pesantren as sites of negotiated gender change within traditional Muslim communities.